2014
DOI: 10.1016/j.biortech.2013.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an external electron acceptor on phosphorus mobility between water and sediments

Abstract: The present work assessed the impact of an external electron acceptor on phosphorus fluxes between water and sediment interface. Microcosm experiments simulating a sediment microbial fuel cell (SMFC) were carried out and phosphorus was extracted by an optimized combination of three methods. Despite the low voltage recorded, ~96 mV (SMFC with carbon paper anode) and ~146 mV (SMFC with stainless steel scourer anode), corresponding to a power density of 1.15 and 0.13 mW/m(2), it was enough to produce an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 19 publications
(31 reference statements)
0
16
0
Order By: Relevance
“…Based on those results, it was decided to change the external resistor from 500 U to 80 U. This change had the purpose of the optimize power production once that the optimum external resistance is the resistance for which the maximum power density was obtained (Martins et al, 2014).…”
Section: Mfc Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on those results, it was decided to change the external resistor from 500 U to 80 U. This change had the purpose of the optimize power production once that the optimum external resistance is the resistance for which the maximum power density was obtained (Martins et al, 2014).…”
Section: Mfc Operationmentioning
confidence: 99%
“…Data were collected automatically and stored in a computer by a USB-9215A BNC connector data logger (National Instruments) and a data acquisition software (Labview 6.0) (Martins et al, 2014). Electrochemical analysis was performed according to Martins et al (2010).…”
Section: Electrochemical and Chemical Analysismentioning
confidence: 99%
“…As repositories of the overlying water body (e.g., oceans, lakes, rivers, or reservoirs), sediments are usually composed of organic and inorganic materials and shelter a complex microbial ecosystem that thrives on several different electron donors and acceptors12.…”
mentioning
confidence: 99%
“…So far, there was no visible loss determined by the naked eye. Once the electrode is optimised a costs benchmark can be done by comparing with more often used electrodes like stainless steel or graphite felt in a similar designed comparable operated system [66][67][68]. Results also showed that the EAB also increased the PU/AC conductivity.…”
Section: Pu/ac Work As a Bioanode And Likely Electrochemically Activmentioning
confidence: 99%